INTEGRAL AND THE CRITICAL POINT MODELS FOR ESTIMATING DAMAGE CAUSED BY WEB BLIGHT ON YIELD AND ITS COMPONENTS ON BEAN - Garcés Fiallos, Felipe Rafael (2014)
Currently there are no studies on the damage caused by Rhizoctonia solani Kuhn [teleomorph Thanatephorus cucumeris (Frank) Donk] on the yield components of common bean (Phaseolus vulgaris L.), therefore the aim of this study was to quantify the reduction in grain yield and its yield components caused by natural infection of web blight in different bean genetic material, in summer 2011, in Quevedo city, Los Rios, Ecuador. Were used lines Cf4 0-0-2-1, Cf6 0-0-4-9, Cf6 0-0-4-8, SER 03 and SER 08, and two varieties FTS Soberano and BRS Valente. Incidence (%) and percentage of severity and number of lesions leaflet-1 were quantified, and these values used to calculate the area under the disease progress curve (AUDPC). Also, it was quantified the number of lesions leaflet-1 during reproductive stages R7 and R8. After harvest, it was quantified the number of nodes, pods and seeds per plant, seeds per pod per plant, and yield (kg ha-1). For estimating the damage caused by the disease were used integral and critical point models, performing regression analysis between disease intensity (independent variables), and grain yield and its components (dependent variable) obtaining the equations of damage function. The results of this research showed that integral and critical point models, are an important tool for estimating damage by web blight on yield components being more evident in the number of seeds per plant (p<0.01).